Development of a Moblie Phone E-Nursing Application Prototype to Improve Self-Care for Heart Failure Patients - Laksmi, Ida Ayu Agung; Susila, I Made Dwie Pradnya; Suprapta, Made Ani (JURNAL INFO KESEHATAN, 2024)
Generally, patients with heart failure will experience activity intolerance resulting in functional limitations and decreased self-care abilities. One of the innovations offered in the Digital era is to develop a mobile phone e-nursing application with mobile technology that can be used by heart failure patients anywhere and anytime. This research aims to create a mobile phone application prototype to improve self-care for heart failure patients. This study is a research and development design. This study involved 32 heart failure patients who had medical records and a history of hospitalization at Mangusada Hospital using a purposive sampling technique. This research produced a prototype the self-care e-nursing application prototype which was developed into 6 main menus including education, weight monitoring, symptom monitoring, diet programs, medication reminders, and rest-activity menus.  Then the prototype was evaluated using the System Usability Scale (SUS) and Post-Study System Usability Questionnaire (PSSUQ). The research results show that the average SUS score reached 84.84 and the overall PSSUQ score was above 5. The conclusion is this prototype is classified as acceptable. Thus, this prototype is worthy of being developed into a real application in the future. Future research is needed to investigate the integration of the e-nursing application with electronic medical records (EMRs) within existing hospital systems.